Implications of Guanidine Substitution on Copper Complexes as Entatic‐State Models. Issue 29 (October 2016) - Hoffmann, Alexander; Stanek, Julia; Dicke, Benjamin; Peters, Laurens; Grimm‐Lebsanft, Benjamin; Wetzel, Alina; Jesser, Anton; Bauer, Matthias; Gnida, Manuel; Meyer‐Klaucke, Wolfram; Rübhausen, Michael; Herres‐Pawlis, Sonja
Abstract: Invited for the cover of this issue is the group of Sonja Herres‐Pawlis from RWTH Aachen University, Germany. The cover image shows our entatic‐state model. The research described in the article is the result of strongly collaborative work of four groups within the interdisciplinary DFG Research Unit FOR1405 ("Dynamics of Electron Transfer Processes within Transition Metal Sites in Biological and Bioinorganic Systems"). Abstract : The entatic state is a tense state, which facilitates reaction in both directions… Read more about the story behind the cover in the Cover Profile and about the research itself onp. 4731 ff .